Peran Data Analytics dalam Meningkatkan Akurasi Pelaporan Pajak Perusahaan di Era Digital pada PT Duta Mahesa Grup - Hendra Dwi Prasetyo; Amin Sadiqin (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
The digital era brings new challenges and opportunities for companies in managing their tax obligations. This study aims to analyse the role of data analytics in improving tax reporting accuracy at PT Duta Mahesa Group. A qualitative approach was used through a case study with primary data obtained from in-depth interviews with the company's finance and taxation team, as well as secondary data in the form of financial and tax reports. The results showed that the implementation of data analytics helped the company identify potential errors, mitigate the risk of inaccurate reporting, and improve the efficiency of the tax data collection process. In addition, this technology also enables faster and more accurate data-driven decision-making. This research concludes that data analytics is a strategic tool to improve tax compliance and optimise tax management at PT Duta Mahesa Group.